Pengaruh Indikator-Indikator Kualitas Layanan dari Bagian Layanan Mahasiswa dan Kualitas Produk Portal Mahasiswa Terhadap Kepuasan Mahasiswa - Hastanti Retno Krisnasari (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This research was aimed to analyze whether Service Quality of Student Service and Quality Product Web influenced Student Satisfaction. Addressing the following questions of Student Service and Quality Product Web to students Strata One Program at Bunda Mulia University in order to find out if they affected student’s satisfaction. The 302 respondents surveyed from 3582 population at academics year of 2011/2012 using Stratified sampling method, which each of study Program were being surveyed averaging 30 respondents per study program. Multiple Regressions estimated technique was employed to analyzing the data using SPSS 16.0 version. The results show that Service Quality of Student Service and Quality Product Web significantly influenced Student Satisfaction. More detailed of Service Quality dimensions significantly influenced student satisfaction are Reliability and Assurance that must be improved by Student Service. While Quality product dimensions which significantly influenced student satisfaction are Reliability Web and Conformance Web that must be improved by Information Technology department.